The Alliance for Healthier Communities' journey to a learning health system in primary care. Issue 1 (28th May 2022) - Nash, Danielle M; Rayner, Jennifer; Bhatti, Sara; Zagar, Lorri; Zwarenstein, Merrick
Abstract: Introduction: The Alliance for Healthier Communities represents community‐governed healthcare organizations in Ontario, Canada including Community Health Centres, which provide primary care to more disadvantaged populations. Methods: In this experience report, we describe the Alliance's journey towards becoming a learning health system using examples for organizational culture, data and analytics, people and partnerships, client engagement, ethics and oversight, evaluation and dissemination, resources, identification and prioritization, and deliverables and impact. Results: Many of the foundational elements for a learning health system were already in place at the Alliance including an integrated and accessible data platform. Leadership championed and embraced the movement towards a learning health system, which led to restructuring of the organization. This included role changes for data support personnel, better communication, and dissemination plans, strategies to engage clinicians and other front‐line staff, restructuring of committees for more collaborative planning and prioritization of quality improvement and research initiatives, and the development of a new Practice‐Based Learning Network for more opportunities to use the data for research and evaluation. Conclusions: Next steps will focus on continued clinical engagement and partnerships as well as ongoing reflection on the transition and success of the learning health system work.